Which Specialty Would You Choose? Understanding Public Preferences for Sleep Disorder Treatment in South Korea - Kim, Jee Hyun; Yang, Tae-Won; Moon, Hye-Jin; Kim, Keun Tae; Cho, Yong Won; Lee, Seo-Young; Lee, Jieon; Cho, Jae Wook (Journal of sleep medicine, 2024)
Objectives: We aimed to investigate public perception of medical specialties in South Korea that diagnose and treat different sleep disorders.Methods: We conducted a web-based survey between January and February 2022, as part of the National Sleep Survey of South Korea 2022. A questionnaire was administered to a stratified, multistage sample of 4,000 random individuals aged 20–69 years from the general population. Participants were asked to select all sleep disorders they believed required treatment from a list. Subsequently, they were asked to identify the clinical department they would visit for each disorder.Results: Sleep apnea (83.4%) and snoring (82.4%) were widely perceived as sleep disorders requiring treatment, followed by insomnia (76.1%), sleepwalking (72.0%), narcolepsy (52.4%), bruxism (49.6%), rapid eye movement sleep behavior disorder (43.4%), excessive daytime sleepiness (33.4%), restless legs syndrome (30.1%), and sleep talking (18.5%). Regarding departments, otorhinolaryngology was the preferred specialty for snoring (79.7%) and sleep apnea (49.4%). More than half of the respondents (55.2%) indicated that they would consult psychiatry department, followed by neurology department (28.2%) for insomnia. Neurology department is preferred for restless legs syndrome, rapid eye movement sleep behavior disorder, excessive daytime sleepiness, and narcolepsy. “Unsure” was a common response for more than 10% of the disorders, excluding snoring and insomnia, highlighting the gaps in public awareness regarding sleep disorders.Conclusions: Public perceptions of the appropriate medical specialties for different sleep disorders vary and are often inconsistent with medical guidelines. Public education regarding the roles of different specialties in managing sleep disorders may improve care by guiding patients to the appropriate specialties.